667 Trends and Patterns of Robotic Assistance in Lumbar Fusion Surgery. (April 2023) - Pando, Alejandro; Hanna, Gabriel; Goldstein, Ira M.
Abstract : INTRODUCTION: Robotic-assisted spine surgery is an emerging field that is growing in utilization. Intraoperative robotic surgical units cost upwards of $600, 000 for medical facilities to purchase. Despite significant cost barriers, these devices are highly marketable for hospitals and physicians. METHODS: The Nationwide Inpatient Sample database from 2016 to 2019 was investigated. Inclusion criteria were patients ≥ 18-years-old who underwent elective lumbar spinal fusion surgery. Trends of robotic-assisted lumbar fusion were examined over time, as well as stratified based on patient and surgical characteristics. RESULTS: A total of 176, 377 patients met the inclusion criteria. The overall rate of robotic-assisted lumbar fusion was 1.2% (2, 131/174, 246). Patients with private insurance were more likely to receive robotic-assisted lumbar fusion (40.3% vs. 37.5%; p < 0.05). Stratifying by race, whites were more likely to receive robotic-assisted lumbar fusion (84.1% vs. 79.5%; p < 0.05). Patients who underwent robotic-assisted lumbar fusion were significantly more likely to have a diagnosis of spondylolisthesis compared to those that underwent traditional lumbar fusion (25.9% vs. 22.0%; p < 0.05). Patients with lumbar fusion done via the anterior approach were more likely to have robotic-assisted surgery compared to other approaches (25.2% vs. 21.3; p < 0.05). Overall, there was a steady increase in its use over time, with patients who underwent lumbar fusion procedures four times more likely to receive robotic-assistance in 2019 compared to 2016 (OR: 4.0; 95% CI: 3.5-4.6; p < 0.0001). Robotic-assisted lumbar fusion was associated with higher inpatient costs ($170, 036.40 vs. $139, 026.10; p < 0.0001) despite having equivalent length of stay (3.31 ± 2.6 vs. 3.37 ± 2.6; p = 0.06). CONCLUSIONS: Robotic-assisted lumbar fusion is on the rise. Patients who had private insurance, were diagnosed with spondylolisthesis, and who had lumbar fusion via the anterior approach were more likely to undergo lumbar fusion using robotic-assistance.